Material Effectiveness Model for the Construction of Aluminum Hull - Suwasono, Bagiyo; Darmawan, Mochammad Rizky; Baroroh, Intan (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2021)
Construction of a hull generally requires several plates and profile material. Early indications for shipbuilding indicate that in manner, the linear function approach for installed material was 75% to 90%, and waste material was 10% to 25%. This study is conducting an assessment of the area of installed material and waste material on small vessels made of aluminum with variations in ship length and the method of approach trend lines both linear and nonlinear. Secondary data retrieval in the form of an aluminum cutting plan for plate material and profile from the AutoCAD application, which is then reprocessed through the FastCAM application to obtain results in the form of identification of installed material and waste material area. Based on variations in ship length and material area results, a scatter plot process was carried out through the Excel application to obtain results in the form of trend line functions with an R-squared determination coefficient of more than 0.9 and the results of the calculation of the intersection between the function of installed material and waste material, and the waste material function with the x-axis uses the balance method. The final result showed that the linear function gives an indication of the effectiveness of the material located in the range of 6 to 23 meters in length of the boat and polynomial function of order 2 in the range of 6 to 18 meters in length, while the waste material area in the two functions maximum 22%.